Association of the polymorphism in the androgen receptor gene and endothelial function in men with type 2 diabetes - Irina Alekseevna Khripun; Sergey Vladislavovich Vorobyev; Michael Iosifovich Kogan (Сахарный диабет)
In recent years, actively studied the effect of androgen deficiency on the cardiovascular system, including endothelial function. Genomic effects of testosterone caused by the length of CAG repeats polymorphism in the androgen receptor (AR) gene.Aim. To examine the association of the polymorphism in the AR gene and carbohydrate, lipid metabolism, endothelial function in men with type 2 diabetes.Materials and methods. We examined 88 men, aged 40-65 years (mean age 53±6,4years) with type 2 diabetes. All patients underwent the study of carbohydrate and lipid metabolism, the assessment of vasomotor endothelial function of the brachial artery by ultrasound sonography, were studied biochemical markers of endothelial dysfunction – ICAM-1, VCAM-1, p-selectin, e-selectin, resistin and number of CAG-repeats in the AR gene. Statistical analysis was performed using the application package SPSS 21,0 using regression analysis.Results. The number of CAG repeats had a significant positive regression to the level of total testosterone, a weak negative regression of the number of CAG repeats in the AR gene and lipid metabolism: triglycerides, LDL, atherogenic index. The assessment of the brachial artery ultrasonography revealed negative regression of the baseline brachial artery diameter and blood flow velocity in the endothelium-dependent vasodilation. The number of CAG repeats was significantly correlated with the levels of p-selectin and resistin. Thus, increasing the number of CAG repeats in the AR gene via a weakening of sensitivity to androgens leads to disruption of endothelial function in men with type 2 diabetes. Increasing the number of CAG repeats in the AR gene leads to deterioration of linear flow velocity during the test with reactive hyperemia with increasing production of p-selectin and resistin.Conclusions. The number of CAG repeats in the AR gene can be regarded as a predictor of the development and progression of cardiovascular lesions in men with type 2 diabetes.